2015
DOI: 10.1177/0960327115597313
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood neutrophil to lymphocyte and platelet to lymphocyte ratios according to plasma glucose status and serum insulin-like growth factor 1 levels in patients with acromegaly

Abstract: Introduction: Cardiovascular, respiratory, and cerebrovascular diseases and malignancies are responsible for morbidity and mortality in acromegaly. Also these diseases are associated with chronic inflammation. The neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) are currently gaining interest as new markers of inflammation. Moreover, increased morbidity and mortality are positively correlated with the presence of diabetes and levels of insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…It is likely that GH and IGF-1 excess has a negative impact on the CV and immune system, which may contribute to the pathogenesis of CVD in patients with acromegaly. However, studies on the role of the immune system in the development of CVD in acromegaly are scarce, and both increased as well as unaltered inflammatory and cardiovascular markers have been reported [21,22,134,136].…”
Section: Perspective On the Role Of Inflammation In The Pathogenesis mentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that GH and IGF-1 excess has a negative impact on the CV and immune system, which may contribute to the pathogenesis of CVD in patients with acromegaly. However, studies on the role of the immune system in the development of CVD in acromegaly are scarce, and both increased as well as unaltered inflammatory and cardiovascular markers have been reported [21,22,134,136].…”
Section: Perspective On the Role Of Inflammation In The Pathogenesis mentioning
confidence: 99%
“…Indeed, in patients with risk factors for atherosclerosis or with established atherosclerosis, circulating monocytes have a pro-inflammatory phenotype, characterized by an increased cytokine production capacity [ 19 , 131 133 ]. It is suggested that this concept may also apply to acromegaly [ 118 , 134 137 ], since GH and IGF-1 have repeatedly been reported to impact on the immune system [ 20 , 138 , 139 ]. Moreover, circulating immune cells express GH and IGF-1 receptors [ 138 , 140 , 141 ], and macrophages and lymphocytes can produce IGF-1 [ 20 , 142 , 143 ].…”
Section: Inflammation In the Pathogenesis Of Atherosclerosis And Cvdmentioning
confidence: 99%
“…Moreover, exposure to IGF1 induces trained immunity (19). However, studies on the inflammatory profile of acromegaly patients rendered conflicting results: both unaltered as well as pro-inflammatory phenotypes have been reported (20, 21, 22). On the other hand, previous studies on the risk of CVD in (treated) acromegaly imply that the arterial structure and function of patients with acromegaly is impaired, which might contribute to the development of CVD (6).…”
Section: Introductionmentioning
confidence: 99%
“…The neutrophil to lymphocyte ratio and platelet to lymphocyte ratio are good markers for inflammation. In their study, Üçler et al [6] demonstrated that there exists a significant positive correlation between the neutrophil to lymphocyte ratio and IGF-1 levels ( p = 0.011) as well as between the platelet to lymphocyte ratio and IGF-1 ( p = 0.035). Acromegaly patients show significant fibrinogen and antithrombin activity, thereby showing an increased tendency to coagulation and enhanced platelet aggregability [7] .…”
Section: Not All Acromegaly Patients Have Leukemiamentioning
confidence: 90%